Self-healing materials from fundamental concepts to advanced space and electronics applications - Aïssa, Brahim; Haddad, Emile; Jamroz, Wez (IET materials, circuits and devices series, 2019)
This book addresses the key concepts of self-healing processes, from their occurrences in nature through to recent advances in academic and industrial research. It includes a detailed description and explanation of a wide range of materials and applications such as polymeric, anticorrosion, smart paints, and carbon nanotubes